The Impact of Auditor's Independence, Ethics, and Competency in Audit Quality: Using Auditor's Integrity as a Mediator in the Sultanate of Oman - Hubais A.S.A.; Kadir M.R.A.; Bilal Z.O. (World Scientific and Engineering Academy and Society, 2024)
Ensuring audit quality is crucial for many parties, including businesses, investors, shareholders, and researchers, who want to focus more on how auditors' input factors affect the quality of their work. The main objective of this study is to analyse the factors affecting the auditor's independence, ethics, and competence in audit quality, with the auditor's integrity as a mediator. The primary data was collected from questionnaires distributed to external auditors in the Sultanate of Oman's private sector with 236 respondents. A Smart-PLS (Partial Least Square) is used to analyse the data. The findings show that the auditor's independence, ethics, and competence significantly impact the audit quality. In addition, the result indicates that the auditor's independence with auditors' integrity as a mediator has a significant impact on audit quality, the auditor's ethics with auditors' integrity as a mediator has a significant effect on audit quality, and the auditors' competence with auditor's integrity as a mediator has a significant impact on audit quality. 2023, World Scientific and Engineering Academy and Society. All rights reserved.